The Application of Nimotuzumab Combined With Definitive Chemoradiotherapy Toward the Treatment of Locally Advanced Cervical Esophageal Carcinoma: A Retrospective Study - Jing Hu; Zhe Chen; Jiaming Lv; Zhen Zheng; Yanping Bei; Xue Chen; Lu Zheng; Wenjie Song; Yunbao Xu (Frontiers in Oncology, 2022)
ObjectiveTo evaluate the safety and effectiveness of nimotuzumab in combination with chemoradiotherapy for locally advanced cervical esophageal squamous cell carcinoma.MethodsRetrospective analysis was conducted from September 2012 to February 2017 among 50 locoregional-advanced cervical esophageal carcinoma (CEC) patients who received concurrent chemoradiotherapy (CRT) combined with or without nimotuzumab at Ningbo Medical Center Lihuili Hospital. Intensity-modulated radiotherapy (IMRT) was administrated on all patients. All patients were divided into two groups, of which 26 (Group A) received 200 mg (22 of 50) or 400 mg (4 of 50) of nimotuzumab per week with CRT and 24 (Group B) received definitive CRT.ResultsThe median follow-up time was 23 months. The median overall survival (OS) and progression-free survival (PFS) were 40.6 and 21.1 months for all, respectively. The 1-, 2-, and 3-year OS rates on the whole were 79.6%, 62.1%, and 47.8%. There was no statistical difference in overall response rate and disease control rate between the two groups. Patients treated with nimotuzumab (group A) had better PFS than the definitive CRT group (group B) (P < 0.05). However, the median OS was 41.4 months in group A and 32.4 months in group B, respectively (P = 0.517). Multivariate analysis showed that PFS among those with lower Eastern Cooperative Oncology Group (ECOG) score (HR = 5.11; P < 0.01), stage II (HR = 9.52; P < 0.01) and the application of nimotuzumab combined with CRT (HR = 0.16; P < 0.01) was much longer. Furthermore, ECOG, stage, C-reactive protein (CRP) baseline, and histological grade can also be used as independent predictors of OS. Grade >3 adverse reactions were not observed. The most common adverse event related to nimotuzumab was mild fever and the occurrence rate was 19% (5 of 26). The incidence of anemia was 65.4% in group A and 87.5% in group B (P < 0.05).ConclusionsFor locoregional-advanced CEC, nimotuzumab combined with IMRT and concomitant chemotherapy was tolerated and effective. In addition, patients with a normal pretherapeutic serum CRP level (CRP < 10 mg/L) can achieve better OS.